2018
DOI: 10.1002/tcr.201700085
|View full text |Cite
|
Sign up to set email alerts
|

Development of Clay‐Based Films

Abstract: Phyllosilicate (clay) is used as a filler to improve the thermal stability and gas barrier properties of plastic films. However, few film preparation trials used clays as the main component. Many researchers have studied clay-based films (CBFs) that are heat-resistant and have high gas barrier properties against various gases (such as oxygen, water vapor, and hydrogen) over a wide range of temperatures. An organic binder improves the film toughness, but increases gas permeation. CBFs are obtained by solution c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 137 publications
(279 reference statements)
0
14
0
Order By: Relevance
“…8 Such high aspect ratio nanosheets are perfectly suited for high-performance polymer nanocomposites as needed for a wide variety of applications, ranging from food packaging all the way to encapsulation of optoelectronic devices like organic photovoltaic and organic light emitting devices. 10 As pointed out by Cussler's theory of the tortuous path 11,12 for optimization of the barrier properties, perfect parallel alignment of the impermeable nanosheets on the substrate is crucial. Parallel aligned (textured) nanosheets are the key to achieve low gas permeabilities as the diffusion pathway for a gas permeant is hereby maximized and the tortuosity strongly decreases once nanosheets become tilted with respect to the diffusion direction (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…8 Such high aspect ratio nanosheets are perfectly suited for high-performance polymer nanocomposites as needed for a wide variety of applications, ranging from food packaging all the way to encapsulation of optoelectronic devices like organic photovoltaic and organic light emitting devices. 10 As pointed out by Cussler's theory of the tortuous path 11,12 for optimization of the barrier properties, perfect parallel alignment of the impermeable nanosheets on the substrate is crucial. Parallel aligned (textured) nanosheets are the key to achieve low gas permeabilities as the diffusion pathway for a gas permeant is hereby maximized and the tortuosity strongly decreases once nanosheets become tilted with respect to the diffusion direction (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The hybrids of water-soluble polymers and smectites have been prepared using preformed polymers and smectites by mixing in aqueous media. Thanks to the homogeneous mixing of water-soluble polymer and smectite in an aqueous media, several forms of the products such as suspension, gel, and solid (powder and film) are available. , Clay-polymer intercalation compounds where polymers are intercalated in the nanospace as molecular thick layers have also been investigated, and the clay-polymer intercalation compounds have been applied as solid-electrolyte (clay-poly­(ethylene oxide)), gas barrier film for food packaging, gasket and optoelectronics devices (clay-poly­(vinyl alcohol)), , precursor of graphitic carbon (clay-polyacrylonitrile), and so on. The superior gas barrier, ionic conduction, chemical stability and/or thermal stability of waterborne polymers were achieved by the intercalation of poly­(acrylic acid) or carboxymethyl cellulose sodium salt, poly­(ethylene oxide), poly­(vinyl alcohol), ,, and polyvinylpyrrolidone into the interlayer space of smectite with keeping the regular layer stacking.…”
Section: Introductionmentioning
confidence: 99%
“…The smectite clay mineral accommodates water in the interlayer space to swell spontaneously, giving a stable aqueous colloidal suspension of anionic clay nanosheets. , Mixing of the pigment with smectite clay minerals in water often results in the stable and homogeneous dispersion, which is useful for paint, cosmetic, and coating application. For example, it was reported that mixing of the clay nanosheet suspension with TiO 2 and subsequent drying resulted in a hybrid film possessing photocatalytic activity, where the clay worked as a binder of TiO 2 . , The smectite clay mineral is also known as an additive/filler to improve material performances such as optical, mechanical, and gas barrier ones of polymers as polymer-clay nanocomposites . Herein, the mixing of chitin with the aqueous colloidal suspension of a smectite clay mineral (synthetic saponite) using a wet-type jet milling is reported to obtain a stable chitin suspension.…”
Section: Introductionmentioning
confidence: 99%
“…35,36 The smectite clay mineral is also known as an additive/filler to improve material performances such as optical, mechanical, and gas barrier ones of polymers as polymer-clay nanocomposites. 37 Herein, the mixing of chitin with the aqueous colloidal suspension of a smectite clay mineral (synthetic saponite) using a wet-type jet milling is reported to obtain a stable chitin suspension. A free-standing chitin/clay hybrid film was successfully prepared by drying the suspension on the polytetrafluoroethylene (PTFE) plate and subsequent peeling off from the substrate.…”
Section: Introductionmentioning
confidence: 99%